Methylation deregulation of miRNA promoters identifies miR124-2 as a survival biomarker in Breast Cancer in very young women - Oltra, Sara S. (Sci Rep, 2018)
MiRNAs are part of the epigenetic machinery, and are also epigenetically modified by DNA methylation. MiRNAs regulate expression of different genes, so any alteration in their methylation status may affect their expression. We aimed to identify methylation differences in miRNA encoding genes in breast cancer affecting women under 35 years old (BCVY), in order to identify potential biomarkers in these patients. In Illumina Infinium MethylationEPIC BeadChip samples (metEPICVal), we analysed the methylation of 9,961 CpG site regulators of miRNA-encoding genes present in the array. We identified 193 differentially methylated CpG sites in BCVY (p-value < 0.05 and methylation differences ±0.1) that regulated 83 unique miRNA encoding genes. We validated 10 CpG sites using two independent datasets based on Infinium Human Methylation 450k array. We tested gene expression of miRNAs with differential methylation in BCVY in a meta-analysis using The Cancer Genome Atlas (TCGA), Clariom D and Affymetrix datasets. Five miRNAs (miR-9, miR-124-2, miR-184, miR-551b and miR-196a-1) were differently expressed (FDR p-value < 0.01). Finally, only miR-124-2 shows a significantly different gene expression by quantitative real-time PCR. MiR-124-hypomethylation presents significantly better survival rates for older patients as opposed to the worse prognosis observed in BCVY, identifying it as a potential specific survival biomarker in BCVY.